THE NOMINAL ROLES OF GERUNDS AND INFINITIVES - Ibrahim, Hussaina (PUPIL: International Journal of Teaching, Education and Learning, 2019)
The theory of the nominal roles of gerundives and infinitives in the production of language has been a subject of researched for nearly a century. Recently, this theory has made serious comeback into the literature with significant a number of published studies. It has been demonstrated that grammatical structures, such as the present tense, future tense, reduce phonologically and morphologically to the point where the lexical items, once viewed as separate entities, have been reanalyzed and have become grammatically cohabited units in which the individual parts are difficult to distinguish and furthermore, this process occurs across languages including English. This paper presents on the nominalization of grammatical processes, in which expressions that are semantically associated with properties are transformed into noun-like expressions. Additionally, the paper pointed out several major difficulties that face an intentional type theoretic notion of property of English predicative constructions. It has also portrayed successful analysis of linguistic syntax on the nominal roles of gerunds and infinitives in English grammar.